2014
DOI: 10.1371/journal.pone.0098614
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of the Rhipicephalus microplus Cytochrome c Oxidase Subunit III Gene Is Associated with a Failure of Anaplasma marginale Transmission

Abstract: Rhipicephalus microplus is an obligate hematophagous ectoparasite of cattle and an important biological vector of Anaplasma marginale in tropical and subtropical regions. The primary determinants for A. marginale transmission are infection of the tick gut, followed by infection of salivary glands. Transmission of A. marginale to cattle occurs via infected saliva delivered during tick feeding. Interference in colonization of either the tick gut or salivary glands can affect transmission of A. marginale to naïve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Clones that code for mitochondrial cytochrome C oxidase subunits I and III appeared at least 10 times. Cytochrome C oxidase, a key mitochondrial enzyme in the respiratory chain, was shown to be important for the transmission of Anaplasma marginale 7 . Several genes coding for the short-chain dehydrogenase family of proteins involved in the metabolism of amino acids, lipids or sugars 8 and for proteins involved in defense responses 9 , bloodmeal digestion 10 , detoxification of endo and xenobiotics 11 , complement inhibition 12 , lipid transport 13 , actin assembly, cell signaling 14 – 16 and for proteins paralogous to secreted salivary proteins including Salp26A 17 were also upregulated by the presence of Borrelia in the tick gut (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Clones that code for mitochondrial cytochrome C oxidase subunits I and III appeared at least 10 times. Cytochrome C oxidase, a key mitochondrial enzyme in the respiratory chain, was shown to be important for the transmission of Anaplasma marginale 7 . Several genes coding for the short-chain dehydrogenase family of proteins involved in the metabolism of amino acids, lipids or sugars 8 and for proteins involved in defense responses 9 , bloodmeal digestion 10 , detoxification of endo and xenobiotics 11 , complement inhibition 12 , lipid transport 13 , actin assembly, cell signaling 14 – 16 and for proteins paralogous to secreted salivary proteins including Salp26A 17 were also upregulated by the presence of Borrelia in the tick gut (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, the knockdown of CYP by RNAi reduced the infection of the mosquito Anopheles gambiae by Plasmodium berghei (Felix and Silveira, 2011). GSTs, which are involved in the detoxification of xenobiotics and oxidative stress (Pavlidi et al, 2018), were also previously reported to be upregulated by infection in arthropods, such as ticks (Mulenga et al, 2003; Mercado-Curiel et al, 2011; Bifano et al, 2014). For instance, one CDS of glutathione S -transferase was upregulated in the cell line BME26 of R. microplus and also in both MG and SG adult males by infection with Anaplasma marginale , the causative agent of bovine anaplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one CDS of glutathione S -transferase was upregulated in the cell line BME26 of R. microplus and also in both MG and SG adult males by infection with Anaplasma marginale , the causative agent of bovine anaplasmosis. However, GST knockdown induced by RNAi presented no effect in either the acquisition of A. marginale by ticks or transmission to calves (Bifano et al, 2014). On the other hand, GST-knockdown reduced the acquisition of A. marginale by the tick D. variabilis , suggesting that the susceptibility response obtained by GST-silencing depends on the tick species and/or the pathogen strain (Kocan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The total number of A. marginale in tick midguts and salivary glands was quantified by qPCR using genomic DNA as template, specific primers ( Supplementary Table 1), and a TaqMan probe that targeted msp5, as detailed by (Bifano et al, 2014).…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%